A indústria de fosfato no Alto Paranaíba e a valorização dos territórios de mineração no contexto da globalização - Silva, Adriano Gonçalves da (2020)
Technical and technological development has made it possible to explore and process various types of minerals used for the manufacture of fertilizers, agrominerals, providing support for geographical expansion and for increasing agribusiness productivity in various territories across the globe. When identifying in its territory large deposits of phosphate rock, which give rise to phosphorus, one of the main macronutrients used in modern agriculture, the Brazilian State in the process of import substitutions implemented several policies that fostered the development of the national phosphate industry with the objective to alleviate external dependence on fertilizer products. The Alto Paranaíba region, in Minas Gerais, was of great importance in this process because it contains the largest phosphate rock reserves in the country. The areas where this mineral production takes place have been integrated with other locations in the Brazilian territory following the expansion of agricultural production in the country. Several rules were created and reformulated to ensure the expansion of capital across the territory and to ensure the performance of transnational groups in Brazil. Technical objects were being installed ensuring this integration and allowing functionality in these areas. In the context of globalization, transnational groups entered the dispute for these areas because Brazil is one of the largest consumers of fertilizers on the planet. In order to meet changes and capital demands, there is a process of valorization and reframing of these areas that accompanies the logic of modernization. In this sense, given the neoliberal logic present in the contemporary period, there has been an overexploitation of natural resources in Brazil that have direct territorial implications in the places where this production occurs.